Produktivitas Mahasiswa di Rumah Selama Masa Pandemi Covid-19 di Tangerang Ditinjau dari Jenis Kelamin - Alfa Annisa, Imarwani; Karjuniwati (Jurnal Riset dan Pengabdian Masyarakat, 2021)
Productivity is a mental attitude. The mental attitude is always looking for improvements to what already exists. a belief that a person can do a better job today than yesterday and tomorrow is better than today. This study aims to determine differences in student productivity at home during the Covid-19 pandemic in Tangerang in terms of gender. The number of respondents in this study was 30 individuals with the criteria of respondents in this study were male students and active female students who live in Tangerang. sampling using purposive sampling. The data analysis used was the independent sample T-test in the SPSS program. based on the results of data analysis the value of Sig. (2-tailed) of 0.863> 0.05, so as the basis for decision making in the independent sample t-test it can be concluded that there is no difference in the average productivity at home between men and women.